الإعراب: خصائصه ومشكلاته - Hairudin Hairudin (Al-Lisan: Jurnal Bahasa, 2020)
Since the beginning of the preparation of Arabic-style and Islamic nuanced science, I’rab has been in the forefront of getting serious attention among Muslim scientists and making it a pillar and foundation in Islamic sciences from various aspects. This is because I'rab has a really essential role in keeping Arabic fluency free from distortion and error, and I'rab will help readers understand religious and non-religious of Arabic texts. This study aims to explore the nature of the I’rab, its specifications, and its problems by focusing on the definition of the I’rab, its emergence, urgency, and its purpose, its correlation, the way of reading and interpretation. The study uses a descriptive method with a literature study that is characterized by inductive, inferential, and exploratory. The result of the study shows that Arabic is pivotal to learn so that Arabic observers avoid mistakes in speaking, especially after the assimilation of Arabic and non-Arab cultures. Furthermore, I’rab also has a crucial position, because it is a science of tools to understand the holy texts of the Qur’an and its interpretations. But unfortunately, not all linguists agree on I’rab’s existence